The Khwajasara Movement and the Challenge of Translocality - Hamzić, Vanja (2014)
This paper offers a critical ethnographic account of the khwajasara movement, based on the author’s most recent fieldwork in Lahore, Pakistan in 2011 and 2012. Khwajasara, known elsewhere in the Indian Subcontinent as hijre (sing. hijra), are Pakistani gender-variant subject position, whose cultural memory and historical roots run deep into the region’s Mughal past (and beyond). This piece attempts to recount khwajasara’s long-lasting social and political battle with the Pakistani judicial and political system, against a backdrop of an important episode in their struggle – the 23 December 2009 judgment of the Supreme Court of Pakistan’s Chief Justice, granting all khwajasara a ‘third gender’ status on their state identification documents – which is yet to be implemented. One of the paradigmatic facets of khwajasara, analysed here primarily as a social and political grassroots movement rather than an essentialised identitary community, is their decidedly subversive approach to collective organising. This approach is operationalised through a number of strategic public actions, including protest marches, domestic litigation and collaboration with workers’ unions, as well as through the everyday classed and gendered life of khwajasara. However, what sets it apart from other social and political movements in the country is its increasingly assertive and commonplace rejection of the prevalent (neoliberal) human rights discourse as well as its non-co-operation with both national and international civil society networks formed around HIV/AIDS prevention industry and/or LGBT community programmes. Based on an analysis of the khwajasara movement’s political and social organising strategies, this paper argues that there is an underexplored potential in studying the class struggle – of which both hegemonic and counter-hegemonic technologies of the self are an integral part – from locale-specific gender-different and gender-variant vantage points. It is posited that khwajasara’s organisational exceptionalism offers a viable ...